Better to regulate pollution sources - Zainudin, Zaki (New Straits Times Press (NSTP), 2014)
MUCH attention has been given to the closure of the Cheras Batu 11 and Bukit Tampoi water treatment plants. The level of ammonia in Sungai Langat at Cheras Batu 11 was reported to have reached 6.4mg/l, whereas at Bukit Tampoi, the level was at 4.2mg/l. These were beyond the acceptable 1.5mg/l. The issue of ammonia, or more scientifically accurate ammoniacal nitrogen or total ammonia nitrogen (TAN), contamination in Klang Valley rivers is long-standing. Throughout the years, a number of cases have been reported in Sungai Selangor and Sungai Langat catchments. The circumstances and source may vary, but in either case, it boils down to the same issue; pollution.